Regional Priority Analysis for Equal Distribution of Educational Facilities in West Java Using the Analytical Hierarchy Process (AHP) Method - Khusaeri, Ahmad (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Inequality in educational infrastructure remains a strategic challenge in West Java Province, where disparities in facility availability across regions hinder equitable access to education. This study aims to analyze and map regional priorities for the development of educational facilities (Elementary to Vocational High Schools) using the Analytical Hierarchy Process (AHP) method. Utilizing secondary data from 27 districts/cities, this study converts school availability data into standardized